L’ambiguità della questione femminile nell’“Orlando furioso”: Una lettura attraverso Marfisa (Ticontre. Teoria Testo Traduzione, 2023)
The aim of this work is the interpretation of the character Marfisa in the Orlando furioso. It is divided in two parts: the first analyzes the character Marfisa, the second focuses on the narrator’s extra-diegetic intevention about women. These two perspectives, separate and independent at first, will collide in the conclusion of the paper in order to offer a general interpretation of the narrator’s erratic actitude towards women in the poem, where praise, accusation and mockery follow one another. This ironic ambiguity, as the work will try to prove, is rather due to aesthetic than ideological reasons: it is actually related to the principle of harmony through compensation on which the whole poem is grounded.